Measuring dishonest behavior: Hidden dimensions that matter. (October 2022) - Gerlach, Philipp; Teodorescu, Kinneret
Abstract: Dishonesty has become a trending topic in the behavioral sciences. To quantify dishonest behavior, various experimental paradigms have been introduced. These experimental paradigms differ along several methodological dimensions. We analyze three such dimensions: elasticity—the resolution with which facts can be misreported, traceability—whether single individuals can be identified as liars, and repetition—the number of opportunities to misrepresent facts. We conclude that differences in these dimensions affect measurements of dishonesty, highlighting the malleability of dishonest behavior. Rather than seeing it as a threat, we argue that dimensional heterogeneity should be harnessed both to better understand the boundary conditions of apparently mixed findings, and to improve the ecological validity of experimental interventions aimed at reducing dishonest behavior.